PROSES ADAT PERKAWINAN SEBAMBANGAN MARGA SEKAMPUNG LIBO DI JABUNG LAMPUNG TIMUR - Nanang Khoirul; Sumiyatun Sumiyatun; Bobi Hidayat (Swarnadwipa, 2019)
The research objective was to describe the traditional marriage process of Sebambangan Marga Sekampung Libo in Negara Batin Village, East Lampung. This research method is qualitative research. Data and data sources are obtained from books, traditional and community leaders and village communities as sources, documentation, and other sources that can assist in gathering research datainformation. Data collection procedures in this study are observation, interviews and documentation. Data analysis was carried out through data collection, data reduction, data presentation, and drawing conclusions and verification. Checking the validity of the findings is carried out through trustworthiness, transferability, accountability, and certainty. The results of research on the sebambangan and its solutions in the indigenous people of Lampung Saibatin Marga Sekampung Libo In Negara Batin Village, East Lampung, there are factors that cause the occurrence of the sebambangan, namely internal factors (consensual, education and age factors) and external factors (economic, parental blessing, social, avoid large costs and compulsion). The implementation of the sebambangan starts when the girl leaves the house with an amount of inheritance money (pengawitan) then muli is taken to the mekhanai family's house and the process is finished. The process of completing a sebambangan is carried out in stages, namely Ngattak Salah, Shooting Bedil, Masang Pajangan, Ngumpul Muwari, Ngayonan, Ngumpul Balak, Sujud, Sesabaian, Canggot, Ijab Kabul, Bathing Belanger / Ngarak, and Awarding of Titles.Keywords: The Traditional Process of Marriage in Sebambangan Lampung Saibatin